(untitled) (Journal of the Bangladesh Agricultural University, 2024)
Pond fish culture is the cornerstone to increase livelihood capitals. This study made an attempt to determine the relationship between livelihood capitals and pond fish culture to measure the changes of livelihoods capitals. The study is based on field survey covering six Upazilas in Mymensingh district of Bangladesh. Only 10 pond fish farmers were randomly selected from 21 villages and stood at 210. Six Key Informant Interview (KII), twenty four FGDs and face to face interviews were done to collect primary information. Analytical technique as ordered probit model was followed to make a relationship between livelihood capitals (financial, natural, physical, human, and social) and pond fish culture. Under physical capitals, sources of credit, input availability and marketing facilities were inadequate in the development of pond fish farmers which directly affects pond fish culture. In terms of the social capital, changes in basic needs, contact with other farmers and political consciousness were significant and positive. In terms of human capital, age, working experiences, and child and adult education were significant and positive but households nutrients and food consumption, visit to health care centre, and water and sanitation conditions were negatively impact on pond fish culture. The overall result of the study found that livelihood capitals were significant and positively impact on pond fish culture. It was, therefore necessary to pay attention on physical, human and financial capitals of pond fish farmers through the provision of institutional credit, training facilities, and market establishment. J Bangladesh Agril Univ 18(4): 1021–1028, 2020 https://doi.org/10.5455/JBAU.111414